Costs of trade and self-selection into exporting and importing: The case of Turkish manufacturing firms - Basak Dalgic; Burcu Fazlioglu; Michael Gasiorek (Kiel Institute for the World Economy (IfW), 2015)
This paper focuses on self-selection into trade by exporting and importing firms, and on the presence of differential variable and sunk costs between exporters and importers across different categories of imports. In addition the authors consider the role of intensive and extensive margins with respect to products or countries. They use a rich and recent dataset for Turkish manufacturing firms for the period 2003-2010. This allows them to provide a comprehensive analysis of firm heterogeneity and the connection between firm-level performance and international trade. They provide evidence on the remarkable heterogeneity across firms where only-importers (importers) perform better than only-exporters (exporters). They detect a self-selection effect for both importing and exporting firms with a stronger effect for importers. The results suggest that the nature of sunk costs varies between importing and exporting activities with importers facing higher sunk costs. Tariffs represent a potentially important source of variation in the variable costs of trading. When taking the tariffs faced by firms into account, the authors find that the self-selection effect associated with sunk costs is still present but greatly reduced with a smaller reduction for importers compared to exporters.
Keywords: D24; F10; M20; L10; 330; firm heterogeneity; self-selection; sunk costs; exports; imports